SEDIMENTOLOGY AND HYDROCARBON RESERVOIR POTENTIAL ASSESSMENT OF PALEOZOIC SANDSTONE OF SERI ISKANDAR, PERAK, MALAYSIA. - ALKHALI, HISSEIN ADOUM (2013)
The clastic rocks outcropping at Seri Iskandar are part of the Paleozoic sedimentary deposits in the Kinta Valley and little is known about these Paleozoic clastic deposits. Over the years, some efforts have been made to evaluate the hydrocarbon potential of pre-Tertiary deposits and initial observation of Paleozoic sedimentary sequences in the Kinta Valley suggests the presence of elements of the Paleozoic hydrocarbon system